Implementation of Independent VAP Prevention Bundle to Prevent Ventilator-Associated Pneumonia (VAP) in Mechanically Ventilated ICU Patients - Lia Azizah; Akhmad Zainur Ridla; Ana Nistiandani; Sugito Tri Gunarto (FORIKES, 2026)
Ventilator-associated pneumonia (VAP) is a nosocomial infection of the lung tissue that most often occurs in patients undergoing mechanical ventilation in intensive care units, with a high morbidity and mortality rate of 1% per day. The incidence of VAP can be prevented through a specific procedure, known as the VAP Bundle. The method in the VAP Bundle includes head-up positioning at 30°-45°, closed suctioning, and oral hygiene using 0.2% chlorhexidine aseptic solution. This study aims to evaluate the effectiveness of the VAP bundle in preventing VAP risk among mechanically ventilated patients at dr. Soebandi Regional Hospital, Jember. This study was a case report involving one patient who met the inclusion and exclusion criteria. The Modified Clinical Pulmonary Infection Score (MCPIS) was measured daily over a six-day intervention period. The results showed that during the six-day intervention, the patient's MCPIS score remained <5 (indicating no VAP). Clinical findings showed no infiltrates, non-purulent secretions, and normalized temperature by intervention end. It can be concluded that the implementation of independent VAP Bundle activities by nurses was successful in preventing VAP among mechanically ventilated ICU patients.Keywords: ventilator-associated pneumonia; head up; suction; oral hygiene; chlorhexidine